TBIO-07. ASSESSING THE UTILITY OF DNA METHYLATION PROFILING IN BRAIN TUMOR DIAGNOSTICS—THE PROSPECTIVE MNP2.0 STUDY. Issue 2 (22nd June 2018) - Sturm, Dominik; Sahm, Felix; Andreiuolo, Felipe; Capper, David; Rode, Agata; Grund, Kerstin; Rutkowski, Stefan; Bison, Brigitte; Gessi, Marco; von Deimling, Andreas; Warmuth-Metz, Monika; Pietsch, Torsten; et al.
Abstract: Children can be affected by a large variety of CNS tumor entities with very divergent outcomes, some of which are exceedingly rare. DNA methylation analysis is a powerful tool to distinguish biologically distinct CNS tumor classes within and across histological entities. The Molecular Neuropathology 2.0 study aims to integrate genome wide (epi-)genetic diagnostics with reference neuropathological assessment for all newly-diagnosed pediatric CNS tumors in Germany. In the first 2 ½ years, 675 patients with sufficient tissue were enrolled from 55 centers. For >95% of patients, a diagnosis according to the WHO classification was assigned by reference neuropathology. Using 10 FFPE sections as input, a DNA methylation-based molecular diagnosis was established in 95% of cases, of which 84% were assigned to a distinct CNS tumor methylation class. The remaining 16% did not match any of 82 currently established classes, with evidence for novel rare entities. Targeted gene panel sequencing of >130 genes performed for 88% of patients with matched blood samples indicated diagnostically, prognostically, or therapeutically relevant somatic alterations in 47%. Germline DNA sequencing data indicated potential predisposition syndromes in 10% of patients. Discrepant results by neuropathological and molecular classification ( 20%) were discussed in a weekly multi-disciplinary tumor board including reference neuroradiological evaluation. Clinical follow-up data for all patients is being collected by the HIT study centers. This ongoing study adds a valuable layer of information to clinical neuropathological diagnostics in Germany and will provide insight into CNS tumors with divergent neuropathological and molecular classification with potential implications for future patient management.